KUALITAS PELAYANAN PAKET LAYANAN KOMPLIT PINDAH DATANG MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS DIAGONAL MODEL - , Nahdhia Nurul Azizah; S. Agus Santoso (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Paket Layanan Komplit is a innovation form Karanganyar civil registry service in order to give civil administration service from anywhere. This innovation undoubtedly facilitates the application process for service seekers. However, there remains an issue with a high percentage of rejections, particularly concerning the “Paket Layanan 2: Pindah Datang”. This is an interesting thing to research, especially how the service quality from “Pindah Datang” service by “Paket Layanan Komplit” is based on the perceptions and expectations of service users. This research measured by using the E-Govqual theory proposed by Papadomichelaki & Mentzas (2012), which consists of indicators such as efficiency, reliability, trust, and citizen support. This research analyze how the quality public service by using descriptive quantitative method with importance performance analysis that consisting of analysis of the suitability level and quadran analysis IPA with diagonal model. The result, suitability level of all attributes is 91,26% which means quite good, with the lowest value is 89,38% on the TR1 attribute (user data is secure) and the higher value is 94.42% on the CS4 attribute (Employees have the ability to convey trust and confidence). The priority improvement in this case is EF7 attributes (Information about field's completion are clear and detailed), RE3 attribute (service process is carried on time), and EF6 attribute (information provided is updated reguraly).